An Examination of Public-Private Partnership in Tourism Development in Nigeria: The “Calabar Carnival” Experience - P. C., Ozili; C. O., Aniagolu; F. O., Maluze (International Journal For Research In Business, Management And Accounting, 2017)
The importance of tourism development in a nation’s economy and sustainable development cannot be overemphasized. The Cross River State Government in Nigeria took the bull by the horn by initiating the “Calabar Carnival” in 2004 with the intention of making the state one of the best tourist destinations in Africa. The Carnival gained popularity but insecurity, poor infrastructural facilities, poor funding amongst others have reduced greatly the progress made by the carnival. This paper therefore tried to X-ray how the success of the carnival could be improved through Public-Private Partnership (PPP). The study adopted the descriptive research method in which data was collected from document of the Cross River State Tourism Bureau (CRSTB), Cross River State Carnival Commission (CRCC) and other published and unpublished materials. The study found out that the carnival has not made serious progress because it is fully organized by CRSTB and CRCC. The study then recommended PPP as a way forward stating that PPP would ensure adequate funding for tourism development in the state, provide tourism support and transport infrastructure while at the same time ensuring security of tourist, maintenance of tourism projects and adequate training of tourism workers to mention only but a few.